1990
DOI: 10.1159/000168120
|View full text |Cite
|
Sign up to set email alerts
|

Normal T Lymphocyte Function in Patients with End-Stage Renal Disease Hemodialyzed with ‘High-Flux’ Polysulfone Membranes

Abstract: T lymphocyte function was analyzed in patients hemodialyzed with ‘high-flux’ polysulfone membranes, which have been reported to improve the patients’ overall clinical condition and well-being. For comparison purposes, patients treated by the use of ‘low-flux’ cuprophane membranes were also studied. Peripheral blood white cell counts, numbers of lymphocytes as well as the numbers of T cells and their CD4 and CD8 subsets were within normal range in both patient groups. The absolute number of B cells was slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…We found no changes in milogen-induced responses, which already before calcitriol therapy were normal. Hemodial ysis with cuprophane membranes have been shown to result in reduced mitogen-induced T-cell responses com pared to dialysis with 'high-flux' polysulfone membranes [24], Only 3 of our patients were dialyzed with cuphrophane membranes, which may explain the overall good mitogen-induced responses. The discrepancy in mitogeninduced responses between the study of Tabata et al [12] and ours is difficult to evaluate since neither the parame ters reflecting their patients' calcium/phosphorus metabo lism and l,25-(OH)2D} levels nor the type of dialysis membranes were given.…”
Section: Discussionmentioning
confidence: 68%
“…We found no changes in milogen-induced responses, which already before calcitriol therapy were normal. Hemodial ysis with cuprophane membranes have been shown to result in reduced mitogen-induced T-cell responses com pared to dialysis with 'high-flux' polysulfone membranes [24], Only 3 of our patients were dialyzed with cuphrophane membranes, which may explain the overall good mitogen-induced responses. The discrepancy in mitogeninduced responses between the study of Tabata et al [12] and ours is difficult to evaluate since neither the parame ters reflecting their patients' calcium/phosphorus metabo lism and l,25-(OH)2D} levels nor the type of dialysis membranes were given.…”
Section: Discussionmentioning
confidence: 68%
“…Comparing recent studies to those performed earlier in the 1980s, the mag nitude of the lymphopenia in HD patients is less striking [13], suggesting that improve ments in dialytic regimens or other aspects of dialysis patient care, such as better control of anemia with erythropoietin, may play a role. Some studies have suggested that frequent blood transfusions augment the lymphopenia of chronic renal failure [14],…”
Section: Lymphocyte Number and Phenotypementioning
confidence: 84%
“…This defect does not correct in patients hemodialyzed with cuprophane membranes al though one recent study suggests that the pro liferative response to high concentrations of PHA normalizes in those patients dialyzed with polysulfone membranes [13]. Abnormal PHA-induced proliferation does not necessar ily signify a T cell defect, since stimulation of proliferation by PHA requires intact accesso ry cell (monocyte/macrophage) function.…”
Section: Proliferation To Mitogensmentioning
confidence: 99%
“…Since changes in im mune competence and lymphocyte functional responses of hemodialyzed patients may be affected by the dialysis membrane used [47], we studied this parameter also in the plasma of patients undergoing hemodialysis by means of cellulose acetate, polyacrylonitrile and polysulfone membranes. The results are summarized in figure 5.…”
Section: Plasma Level O F Soluble Il-2 Receptor In Hemodialysis Patientsmentioning
confidence: 99%